An investigation into the pharmaceutical advertising in Iranian medical journals - Nazila Yousefi; Zahra Sharif; Fateme Chahian; Tayebe Mombeini; Farzad Peiravian (Taylor & Francis Group, 2022)
Background Pharmaceutical advertising is not only considered a key factor in the successful launch of pharmaceutical products, but is also an important source of public health information with a significant impact on consumer choice and behavior. Nowadays, advertising has become the broadest dissemination channel for various products, including medicines, which may ultimately lead to the generalization of self-treatment or mistreatment. Improper drug promotion can exacerbate unhealthy outcomes by making false or misleading claims, using inferior references, and failing to meet international standards. This study aimed to examine the requirements for pharmaceutical advertising from regulatory perspective and the compliance of Iranian pharmaceutical advertisements to related standards and guidelines. It is limited to print advertisements in Iranian national medical journals and magazines. Method The present study is a descriptive-analytical study using bibliometric methods. As a first step, a comprehensive review of the national and international regulations on drug advertising was conducted and a comparison of different regulations was provided. In the second step, a checklist was created to evaluate the compliance of drug advertising with the extracted regulations. Result The results of the present study show that the claims made in Iranian drug advertisements are 29.10% valid, 27.67% exaggerated, 23.10% controversial, 12.62% misleading, and 6.8% invalid. In general, we found that most medical advertisements in Iranian journals and magazines comply with national laws and regulations. However, many international requirements are not met in these advertisements. Conclusions Although we found that printed medical advertisements in Iran are roughly compliant with national regulations, there is still a long way to achieve full compliance. Monitoring processes should be improved and clearly defined penalties should be set to avoid misleading claims and their likely health consequences. It is very important in Iran to update the existing rules and regulations for medical advertisements according to international guidelines. More careful monitoring of the content of advertising and the accuracy of claims are also needed.